Pathophysiological status and nutritional therapy of peptic ulcer: An update - Mayank Kulshreshtha; Gunja Srivastava; Manjul Pratap Singh (Environmental Disease, 2017)
Peptic ulcer (PU) is the most common disease of gastrointestinal tract (GIT) which affects the stomach and duodenum. It is characterized by an imbalance between the aggressive and defensive factors. Lifestyle and eating habits play an important role in the case of PU. According to the latest World Health Organization data published in April 2011, PU disease deaths in India reached 108,392 or 1.20% of the total deaths. The age-adjusted death rate is 12.37/100,000 of population, which leads India to 5th rank in the world. The aim of this review was to summarize the scientific data, herbal research, nutritional therapy, precautions, and pharmacological/nonpharmacological treatment regarding PU. The update conclusion regarding PU therapy was concluded with the help of published scientific data on Pub Med, Google Scholar, Med Know, Elsevier and other online resources. Natural remedies are found to be safe (minimum side effects) whereas, in allopathic treatment, antacids with the combination of proton pump inhibitors can better control PU. A balanced dietary plan should be advised by health care professionals or providers to patients suffering from PU. Following good habits and avoiding spicy food make our GIT healthy. Hence, a better lifestyle automatically cures the PU. Better knowledge with balanced lifestyle is an excellent treatment of PU.